EPIDEMIOLOGICAL INDICATORS PREDICTING THE HIGH-TECHNOLOGICAL TYPES OF MEDICAL CARE VOLUMES IN BREAST CANCER CASES - N. S. Romanenkov; K. N. Movchan; V. V. Hizha; Yu. M. Morozov; A. V. Zharkov; O. I. Yakovenko; E. V. Zheleznyj (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
Introduction. The diagnostic possibilities for breast cancer (BC) are expanding. The results of BC patients treatment are also improving. The 5-year survival rate in BC patients is increasing. The number of mastectomy (ME) in BC patients does  not decrease. Therefore, the BC epidemiological data analysis in the female population of Russia is in demand to predict the need of the volumes of the breast reconstruction after ME.Methods and materials. A retrospective cohort study was conducted. The information on BC cases in St. Petersburg residents in 2011–2018 yr. was analyzed. Statistical processing was carried out using the programs Statistica 12.0 for Windows, «Population cancer registry».Resalts and discussion. In 2017 yr., in St. Petersburg, the incidence of BC was 60.11 0/0000. The prevalence of BC in the analyzed period is higher than the national indicator by 19.3 %. In 2018 yr., women of working age were diagnosed with BC 16.6 % more often than in 2011. The frequency of the I–II stage BC verification in 2011 – 2018 yr. increased 1.2 times, reaching 72.2 % in 2018 yr. In 2018 yr., the 5-year survival rate in BC patients was 63.4 %.Conclusion. In connection with the annual increase in the number of BC patients undergoing ME, it is reasonable to expect an increase in potential needs for breast reconstruction, which will necessitate the expansion of the volume of hightech types of medical care provided to BC patients.